2012
DOI: 10.1111/jppi.12009
|View full text |Cite
|
Sign up to set email alerts
|

Lecturer Responses to the Inclusion of Students With Intellectual Disabilities Auditing Undergraduate Classes

Abstract: Although postsecondary education for people with intellectual disabilities can improve their chances of employment and create a more satisfying life, higher education is becoming a more usual avenue of postschool learning. As part of a 2‐year Certificate in Contemporary Living (CCL) Program offered at Trinity College Dublin, students audited undergraduate university courses, partly with assistance of class peer mentors. The study sought to explore the views of university lecturers whose classes the students at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 11 publications
2
43
0
Order By: Relevance
“…Only 3% of PSE directors identified faculty burden as a major barrier to their program at the present time, while 88% rated individual faculty members as supportive or extremely supportive at the present time and 76% of academic departments were currently rated as supportive or extremely supportive. As noted in the literature review, individual program reports on faculty enthusiasm and participation were somewhat equivocal at first, but it is highly likely that, nationwide, efforts to support and educate faculty have addressed many concerns (CaustonTheoharis et al, 2009;Haffner et al, 2011;O'Connor et al, 2012) As also indicated in the literature, faculty support was identified as a strength, particularly when supported by preparation and participation in faculty-related decisions (Uditsky & Hughson, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Only 3% of PSE directors identified faculty burden as a major barrier to their program at the present time, while 88% rated individual faculty members as supportive or extremely supportive at the present time and 76% of academic departments were currently rated as supportive or extremely supportive. As noted in the literature review, individual program reports on faculty enthusiasm and participation were somewhat equivocal at first, but it is highly likely that, nationwide, efforts to support and educate faculty have addressed many concerns (CaustonTheoharis et al, 2009;Haffner et al, 2011;O'Connor et al, 2012) As also indicated in the literature, faculty support was identified as a strength, particularly when supported by preparation and participation in faculty-related decisions (Uditsky & Hughson, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…Although faculty reluctance was identified as a barrier, the faculty interviewed in this study were open to and supportive of the PSE program; their reluctance stemmed from fear that they were not adequately trained or qualified to work with students with IDD. O'Connor, Kubiak, Espiner, and O'Brien (2012) also reported strong support from faculty and a willingness to be flexible in course delivery in a qualitative study conducted at a university in Ireland. The researchers reported that program support was built on a strong foundation of social justice embraced by the faculty interviewed.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…At Trinity College, Dublin, the two-year educational program "Certificate in Contemporary Living" (CCL) has been in place since 2005 for people with intellectual disability (O'Connor et al, 2012). The aim of this program is to promote inclusion for PWID through a syllabus of ten subjects, of which two are optional.…”
Section: Irelandmentioning
confidence: 99%
“…One major problem concerns the composition of the sample of participants. Examples of commonly encountered disabilities in higher education include autism, psychiatric disorders, learning disabilities, sensory deficits, and motor deficits (De Cesarei, 2015;Morris & Turnbull, 2007;Nevill & White, 2011;O'Connor, Kubiak, Espiner, & O'Brien, 2012). Each type of disability poses specific challenges related to the type and severity of the impact on the student's life, the psychological impact of the disability, and the stigma associated with it (Fevre, Robinson, Lewis, & Jones, 2013;Kuruvilla & Joseph, 1999).…”
Section: Introductionmentioning
confidence: 98%